Optimization of Fiber Factors on Flexural Properties for Carbon Fiber Reinforced Polypropylene - Nugroho, Gesang; Budiyantoro, Cahyo (MDPI AG, 2022)
Fiber factor strongly influences the flexural properties of fiber-reinforced composites. Theo-retically, strong fiber-matrix bonds combined with long fibers can produce high composite strength, while short fibers influence the ductility of the composite. Both conditions are obtained by aligning the fiber with the loading direction. In this study, an experimental study was conducted on the effect of fiber factors on the flexural strength and modulus of carbon fiber reinforced polypropylene. The fiber factors included in this study were: cryogenic fiber surface treatment, fiber length, and fiber orientation; each factor was divided into three levels. The relationship between the fiber factors and the responses was analyzed using the Response Surface Method (RSM) and Analysis of Variance (ANOVA). The results indicate that there is a good correlation between the predicted response values of the model and the results of the confirmation test. The fiber orientation has the most significant effect on the flexural strength of the composite. All fiber factors significantly affected flexural modulus, with fiber orientation as the most significant factor. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.